A review of enhanced municipal wastewater treatment through energy savings and carbon recovery to reduce discharge and CO2 footprint. (November 2022) - Du, Rui; Li, Cong; Liu, Qingtao; Fan, Jiarui; Peng, Yongzhen
Graphical abstract: Highlights: Current biological processes in WWTPs are being challenged by sustainability. Anammox-based energy-saving processes are reviewed. HRAS followed with anaerobic fermentation processes for carbon recovery are discussed. Integration of energy-saving and carbon recovery processes is prospected. Future research toward ultimate carbon neutrality goals is discussed. Abstract: Municipal wastewater treatment that mainly performed by conventional activated sludge (CAS) process faces the challenge of intensive aeration-associated energy consumption for oxidation of organics and ammonium, contributing to significant directly/indirectly greenhouse gas (GHG) emissions from energy use, which hinders the achievement of carbon neutral, the top priority mission in the coming decades to cope with the global climate change. Therefore, this article aimed to offer a comprehensive analysis of recently developed biological treatment processes with the focus on reducing discharge and CO2 footprint. The biotechnologies including "Zero Carbon", "Low Carbon", "Carbon Capture and Utilization" are discussed, it suggested that, by integrating these processes with energy-saving and carbon recovery, the challenges faced in current wastewater treatment plants can be overcome, and a carbon–neutral even be possible. Future research should investigate the integration of these methods and improve anammox contribution as well as minimize organics lost under different scales.